Saturday

July 26, 2014

July 26, 2014

Posted by **413** on Tuesday, October 24, 2006 at 1:28pm.

f(x)= e^-x^2.

I got f''(x)=-2e^-x^2 + 4x^2e^-x^2

i need some help on find f''''(x)

You have

f(x) = e

f'(x) = -2x*e

f"(x) = (4x

f"'(x)= f'(x)*(4x

f(x)(-8x

f""(x) = f'(x)*(-8x

-2x*f(x)(-8x

f(x)(16x

Be sure to verify my algebra.

**Related Questions**

Property of logarithms - Using property of logarithms, how do I prove derivative...

Powers in Math - (5a^3b^4)^2=? *I don't get this one...PLease Help! (5a3b4)2= (5...

math-volume - I'm confused with how to solve this problem, so help would be ...

help - Y^3Y/Y^-2 If you post with the correct word in the Subject line, you'll ...

Calculus - Use implicit differentiation to find the slope of the tangent line to...

Chemistry - Sorry for posting this again, I dont know if the question was ...

Math - If a^3 = x^2 what is a^2y+1 = x^6, solving for y You would have (x2)3 = ...

algebra 2 - divid 4/x^7 by 12/x^5 I got this far but Got lost can some help me 4...

mat 117/ algebra - My question is about scientific notations. Here is the ...

chemistry equation - Write a net ionic equation for the reaction of iron(III)...